STUDENT READINESS AND CHALLENGE IN COMPLETING HIGHER ORDER THINKING SKILL TEST TYPE FOR MATHEMATICS - Kusaeri Kusaeri; Asep Saepul Hamdani; Suprananto Suprananto (Jurnal Infinity, 2019)
Mathematics teaching and learning should equip students with the ability to think critically and creatively and problem-solving skill to enable them to compete in the industrial revolution 4.0. This descriptive explorative study explores the readiness and challenges faced by Indonesian junior high school (SMP/MTs) student in solving HOTs type mathematics test using Islamic context. Data were collected from a test-based open-ended questionnaire distributed to 164 students in the 8th of five schools in Sidoarjo East Java comprising 2 junior madrasas (Islamic schools), 2 Islamic-based junior high schools and 1 public junior high school. Descriptive analysis using SPSS and categorization of responses (referring to response options in the questionnaire such as have ever-never, necessary-unnecessary, answered-not answered, etc) show that considering their experience, the students are â€œless readyâ€ to face HOTs type mathematics test. However, students expect that they can be given more practices in doing HOTs type mathematics questions to help them get accustomed to this type of question. Being unaccustomed to non-routine and lengthy questions, lazy trait and being unfamiliar to Islamic terms used as the context of the question becomes the challenges for the students in facing HOTs type mathematics test.